Patterns of butterfly biodiversity in three tropical habitats of the eastern part of Western Ghats - S, Murugesan; M, Muthusamy (Journal of Research in Biology, 2011)
The Western Ghats is one among the hot spots in 25 biodiversity countries identified in the world. The Coimbatore city is situated at the foot hills of Western Ghats (a part of Nilgiri Biosphere Reserve) are recognized as a paradise of butterflies due to its salubrious climate. Butterflies in the Western Ghats belong to 5 families, 166 genera and 330 species, of which 37 species are endemic and they depend on more than 1000 plant species for feeding and breeding. The present study surveyed 103 individual butterfly species belonging to 5 families namely Nymphalidae (32), Pieridae (23), Lycaenidae (19), Hesperiidae (15) and Papilionidae (14), which revealed that Nymphalidae and Pieridae are the rich dominant families, while Hesperiidae and Papilionidae are less dominant. High incidences of butterfly population with wide distribution were observed during the months of March-April and the monsoon seasons (September - November) which diminish during December-January. It was observed that the occurrence and distribution of butterflies are closely associated with the availability of its larval and adult host plants. The butterfly population of a species is gradually decreasing in number due to human interference in the habitat and the destruction of host plants.